Socio-demography factors that influence youth attitude towards contract farming - Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril; Uli, Jegak; Abu Samah, Bahaman (Science Publications, 2010)
Malaysia is one of the developing countries that rely on agriculture to boost its economy sector. This can be proved through The Ninth Malaysia Plan where agriculture is planned to be the third income generator of the country. Contract farming is one of the potential agriculture activities that proffers propel maximization of production and enhancing economic and social conditions among the farming communities. This innovative and economic viable farming opportunity indeed depends on the commitment of youth since they are the pillar to the sustainability of agriculture. However, do youth in Malaysia have a positive attitude towards contract farming? Approach: This study is a quantitative study, using a pre tested and developed questionnaire. This study inspected the attitude of Malaysian youths toward contract farming and socio-demography factors that affect it. A sample random sampling were performed where a total of 400 undergraduates were selected to be the respondents of the study. The data were analyzed using PASW software. Results: Results gained depicted that youths have a positive attitude towards contract farming. Moreover, from the independent t-test and ANOVA test done, it can be concluded that information regarding contract farming, type of course taken and university where the students study play a major role in influencing their attitude towards contract farming. Conclusion/Recommendations: From the results gained it can be concluded that information, course taken and universities where they learn can influence youth acceptance towards contract farming. It can be noted that specific course on contract farming can be established within selected universities in order to expose contract farming to the youth. It was recommended that a specific study on the role of universities in creating a better attitude among youth should be conducted.